Quantification of morpho-hemodynamic changes in unruptured intracranial aneurysms with irregular pulsation during the cardiac cycle using 4D-CTA - Chen, Shiyao; Zhang, Wen; Cheng, Yunzhang; Wang, Guohui; Lv, Nan (Frontiers in Neurology, 2024)
Background and Purpose: Previous studies predicting the rupture risk of intracranial aneurysms (IAs) have predominantly utilized static imaging data, overlooking the dynamic blood flow and biomechanical properties of the aneurysm wall. Irregular pulsation detected by 4D-CTA is a potential predictor of aneurysm rupture, albeit with uncertain clinical significance. This study aimed to analyze the changes in morpho-hemodynamic characteristics of IAs during the cardiac cycle to elucidate the dynamic changes and the associated hemodynamic mechanisms. Methods: A retrospective review was conducted on the 4D-CTA data of IA patients between January 2017 and September 2019. R-R intervals were segmented into 20-time phases, reconstructing 20 CT datasets to identify irregular pulsation and extract 3D aneurysm models. Computational fluid dynamics (CFD) simulations analyzed hemodynamic parameters such as oscillatory shear index (OSI) and relative residence time (RRT). Changes in morpho-hemodynamic characteristics were quantified in terms of the absolute change (parameter*) and relative change rate (parameter%). Rupture risk was assessed using the rupture resemblance model (RRS). Results: Eleven UIAs from 10 patients were finally included, with five aneurysms showing irregular pulsation (45.45%). No significant differences in morpho-hemodynamic characteristics were observed between aneurysms with or without irregular pulsation. More remarkable changes in aneurysm size (size*: 0.59±0.14 mm vs. 0.32±0.12 mm, P = 0.010; size%: 10.49%±1.43% vs. 3.95%±1.79%, P < 0.001), volume (volume%: 13.72% vs. 6.39%, P = 0.009), OSI (OSI*: 0.02±0.01 vs. 0.004±0.005, P = 0.004; OSI%: 200% vs. 12.50%, P = 0.004) and RRT (RRT%: 97.14% vs. 43.95%, P = 0.052) over the cardiac cycle were significantly linked to irregular pulsation. Aneurysms with irregular pulsation demonstrated a more unfavorable hemodynamic environment during the cardiac cycle, irrespective of the predicted rupture risk. Furthermore, irregular pulsation at the aneurysm dome exhibited higher hemodynamic instability than at the sidewall. Conclusions: Irregular pulsation may indicate hemodynamic instability within the aneurysm, leading to an increased rupture risk in the area where irregular pulsation occurs. This proof-of-concept study could enhance understanding of dynamic changes in UIAs during the cardiac cycle and the underlying hemodynamic mechanisms.